2017
DOI: 10.1111/glob.12160
|View full text |Cite
|
Sign up to set email alerts
|

A great leap? Domestic market growth and local state support in the upgrading of China's LED lighting industry

Abstract: In this article we analyse the conditions for industrial upgrading in the Chinese LED industry, which proactive local state policies and expanding domestic markets have greatly facilitated. State initiatives provoked overinvestment, but eventually led to the emergence of competitive domestic enterprises. Simultaneously, firms benefited from a growing domestic market on which they outcompeted foreign companies in mid‐price segments. The combination of these factors accounts for the peculiarly Chinese upgrading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In a different sector, Chinese firms such as Lenovo and Ziiguang turned to original brand manufacturing (OBM) by supplying the domestic market -and learning relevant technology and marketing expertise -while also accessing knowledge from supplying the global market (Zhou 2008(Zhou : 2365. Thus, some authors have suggested that participating in and creating domestically-oriented VCs or PNs could be a key avenue for upgrading (Butollo and Ten Brink 2017) -a different emphasis from the earlier GVC literature. More broadly, upgrading considerations in the Global South must continue to consider not only social and environmental dimensions, but also markets beyond the Global North as part of a wider approach that explores VCs and PNs oriented towards different end markets.…”
Section: Reconsidering Upgrading Within Polycentric Tradementioning
confidence: 99%
“…In a different sector, Chinese firms such as Lenovo and Ziiguang turned to original brand manufacturing (OBM) by supplying the domestic market -and learning relevant technology and marketing expertise -while also accessing knowledge from supplying the global market (Zhou 2008(Zhou : 2365. Thus, some authors have suggested that participating in and creating domestically-oriented VCs or PNs could be a key avenue for upgrading (Butollo and Ten Brink 2017) -a different emphasis from the earlier GVC literature. More broadly, upgrading considerations in the Global South must continue to consider not only social and environmental dimensions, but also markets beyond the Global North as part of a wider approach that explores VCs and PNs oriented towards different end markets.…”
Section: Reconsidering Upgrading Within Polycentric Tradementioning
confidence: 99%
“…In the majority of cases analyzed wherein the state has played a facilitating role, a variety of economic upgrading outcomes have been identified, particularly regarding product or inter-chain upgrading (see Table 4). This is especially apparent in relation to strengthening links between research institutions and local companies (knowledge infrastructure), to enable local firms to enter new industries and adopt more value-added activities (e.g., Bȃzȃvan, 2019;Butollo & Ten Brink, 2018). A case in point is the Penang Export Hub, where a stateprogram was launched specifically to support firm innovation, access to markets and advanced technologies in the electronics sector to boost local R&D capabilities (see Athukorala, 2014;Athukorala, 2017).…”
Section: State As Facilitatormentioning
confidence: 99%
“…The stringency of the regulatory framework is found to be especially effective in supporting product upgrading (see Table 4). The setting of quality or price standards (e.g., Behuria, 2019) and/ or banning specific (low-value) technologies (e.g., Butollo & Ten Brink, 2018), can foster shifts in local production toward higher value-added products. State regulation has also been associated with improved social conditions, requiring or supporting the adoption of internationally or locally developed certification schemes (Behuria, 2019;Schouten & Hospes, 2018); and through stricter enforcement of labor regulation (e.g., Braun-Munzinger, 2019;Hossain, 2019).…”
Section: State As Regulatormentioning
confidence: 99%
See 2 more Smart Citations